Mode II fracture of an elastic-plastic sandwich layer - Martínez-Pañeda, E; Cuesta, II; Fleck, N (ASME International, 2019)
The shear strength of a pre-cracked sandwich layer is predicted, assuming that the layer is linear elastic or elastic-plastic, with yielding characterized either by the J2 plasticity theory or by a strip-yield model. The substrates are elastic and of dissimilar modulus to that of the layer. Two geometries are analyzed: (i) a semi-infinite crack in a sandwich layer, subjected to a remote mode II K-field and (ii) a center-cracked sandwich plate of finite width under remote shear stress. For the semi-infinite crack, the near-tip stress field is determined as a function of elastic mismatch, and crack tip plasticity is either prevented (the elastic case) or duly accounted for (the elastic-plastic case). Analytical and numerical solutions are then obtained for the center-cracked sandwich plate of the finite width. First, a mode II K-calibration is obtained for a finite crack in the elastic sandwich layer. Second, the analysis is extended to account for crack tip plasticity via a mode II strip-yield model of finite strength and finite toughness. The analytical predictions are verified by finite element simulations, and a failure map is constructed in terms of specimen geometry and crack length.